2014
DOI: 10.1007/s10549-014-2967-x
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum stress markers GRP78 and CHOP predict disease-free survival and responsiveness to chemotherapy in breast cancer

Abstract: Glucose-regulated protein (GRP) 78 and C/-EBP homologous protein (CHOP) are commonly used as markers of endoplasmic reticulum (ER) stress. As an ER chaperone, GRP78 functions as a potent anti-apoptotic factor and confers drug resistance, whereas CHOP is a key initiating factor of ER stress-related cell death. We aimed at investigating the predictive values of GRP78 and CHOP in breast cancer patients who underwent adjuvant chemotherapy. An immunohistochemistry screen for GRP78 and CHOP was performed using a tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 21 publications
0
61
1
Order By: Relevance
“…According to the previous study, cancer cells are usually under endoplasmic reticulum stress (ERS) and they are in a need of a highly specific ER quality-control system which is also named as the unfolded protein response (UPR) to maintain ER homeostasis. 9 In recent years, it has been found that ERS could directly induce autophagy for protein restoration by synthesizing unfolded, misfolded, and damaged proteins and subsequently inducing UPR-mediated upregulation of binding immunoglobulin protein (BiP), which is the dispensable autophagosome formation. 10 Interestingly, the cells' ability of responding to ERS is essential for their survivals, and chronic or unresolved ERS can result in cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous study, cancer cells are usually under endoplasmic reticulum stress (ERS) and they are in a need of a highly specific ER quality-control system which is also named as the unfolded protein response (UPR) to maintain ER homeostasis. 9 In recent years, it has been found that ERS could directly induce autophagy for protein restoration by synthesizing unfolded, misfolded, and damaged proteins and subsequently inducing UPR-mediated upregulation of binding immunoglobulin protein (BiP), which is the dispensable autophagosome formation. 10 Interestingly, the cells' ability of responding to ERS is essential for their survivals, and chronic or unresolved ERS can result in cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 193 cancerous and 36 noncancerous mammary cases were included in IHC analyses. IHC variables were scored semiquantitatively according to the approach of a prior study (21). The brief details of TMAs construction, IHC staining, and IHC variable evaluation are described in the Supplementary Methods.…”
Section: Tissue Microarray Ihc Staining and Ihc Variable Evaluationmentioning
confidence: 99%
“…The UPR initially functions as an adaptive response, but it might trigger apoptosis under prolonged or severe ER stress. ER stress also upregulates CHOP, and thus this molecule is used as another ER stress marker [40]. To investigate whether AOPPs induced ER stress in podocytes, we examined the expression of GRP78 and CHOP by performing RT-PCR and Western blot assays.…”
Section: Aopps Induced Er Stress In Podocytesmentioning
confidence: 99%